An Energetic (Nitro‐NNO‐azoxy)triazolo‐1, 2, 4‐triazine. Issue 26 (13th June 2019) - Anikin, Oleg V.; Leonov, Nikita E.; Klenov, Michael S.; Churakov, Aleksandr M.; Voronin, Alexey A.; Muravyev, Nikita V.; Strelenko, Yurii A.; Fedyanin, Ivan V.; Tartakovsky, Vladimir A.
Abstract : 7‐Nitro‐3‐(nitro‐ NNO ‐azoxy)[1, 2, 4]triazolo[5, 1‐ c ][1, 2, 4]‐triazin‐4‐amine (4 ) is the first high‐melting compound bearing adjacent nitro‐ NNO ‐azoxy and amino groups. It was synthesized by nitration of 7‐nitro‐3‐( tert ‐butyl‐ NNO ‐azoxy)[1, 2, 4]triazolo[5, 1‐ c ][1, 2, 4]triazin‐4‐amine (3 ) with NO2 BF4 . Compound 4 is a rather thermally stable (decomposition onset temperature 154 °C), highly energetic (calculated heat of formation 580 kcal· kg –1 ), and highly dense (1.875 g cm –3 ) material with a CO‐level oxygen balance. Abstract : A method for the synthesis of a novel energetic compound, 7‐nitro‐3‐(nitro‐ NNO ‐azoxy)‐[1, 2, 4]triazolo[5, 1‐ c ][1, 2, 4]triazin‐4‐amine, bearing adjacent nitro‐ NNO ‐azoxy and amine groups has been elaborated. It is a rather thermally stable (decomposition onset temperature 154 °C), highly energetic (calculated heat of formation 580 kcal· kg –1 ), and highly dense (1.875 g cm –3 ) material with a CO‐level oxygen balance.